Pelatihan Penulisan Karya Ilmiah, Buku, dan Publikasi bagi Mahasiswa Calon Sarjana: Digitalisasi Literasi Akademik - Wekke, Ismail Suardi; Andi Sumangelipu; Muzakkir (Compile Journal of Society Service, 2025)
Writing scientific papers, books, and publications is an important part of the academic world, especially for undergraduate students. These competencies not only support graduation but also increase competitiveness in the world of work and scientific contributions to society. This article describes the training activities for writing scientific papers, books, and publications carried out as part of community service. The purpose of this activity is to improve student's skills in writing scientific papers and publishing them in relevant media by utilizing digital applications. This training includes an introduction to the basics of academic writing, the structure of scientific papers, editing techniques, and publication strategies. The results of this activity show an increase in students' understanding and ability to produce quality writing and higher motivation to contribute to the academic world.